Integrasi Teknologi Informasi dalam Tata Kelola Data Pendidikan: Strategi Peningkatan Akuntabilitas Pelayanan di Kabupaten Sidoarjo - Hasan Bisri; Ika Devy Pramudiana; Aris Sunarya (Asosiasi Ilmuwan Pendidikan, Sosial, dan Humaniora Indonesia, 2025)
This research seeks to examine the incorporation of information technology in educational data management as a tactic to improve public service accountability in Sidoarjo Regency. The context of this study stems from the regional government’s requirement to enhance educational data management systems that are still only partially integrated and lack transparency for making decisions based on evidence. By implementing interconnected digital educational systems, Sidoarjo aims to create effective, transparent, and performance-driven governance. Employing a qualitative case study methodology, this study included participants from the Department of Education and Culture, school administrators, data managers, digital system creators, and members of the community. Data were gathered through thorough interviews, observations, and examination of documents related to policies on educational digitalization. The results show that the incorporation of information technology has enhanced administrative efficiency, accuracy in reporting, and public access to educational data. Nonetheless, obstacles persist in digital literacy, uneven infrastructure across schools, and restricted coordination between agencies. The research emphasizes the significance of teamwork in leadership, clear processes, and community involvement in enhancing public accountability. Suggestions involve establishing a regional education data center and ongoing training initiatives for teachers to maintain thorough digital transformation within the Sidoarjo education framework